Economic Empowerment Strategy for Students and Alumni of Islamic Boarding School through the Community-Based Work Training Center - Edi Nur Prasetyo; Annisa Fitria Dian Soleha (LifeSciFi, 2026)
This study is grounded in the large number of Islamic boarding schools in Indonesia, which have not been fully matched by the economic readiness of their graduates to compete in the modern labor market. The community training center program emerges as a policy innovation that integrates vocational education with Islamic boarding school values. This study aims to analyze the strategies of economic empowerment of Islamic boarding schools graduates through the implementation of the Community Training Center Program and to examine its implications for their socio-economic welfare. A qualitative approach with a multi-site case study design was employed in two Islamic boarding schools in Blitar City. Data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that both BLKKs implement asset-based planning, instructor capacity strengthening, sustainable facility management, learning-by-doing training methods, post-training mentoring, multi-stakeholder partnerships, and learning-oriented monitoring and evaluation. The program significantly improves alumni technical and non-technical skills, expands employment and entrepreneurship opportunities, and enhances income as well as multidimensional welfare. These findings imply that strengthening community-based vocational training in Islamic boarding schools can serve as an effective strategy for promoting sustainable economic empowerment and inclusive local development.